PENANAMAN KARAKTER RELIGIUS MELALUI BUDAYA SEKOLAH DI MI NW BAGIK NYALA - Zulfa, Indana; Helmi Najamudin; Hilyatuzzohrah Muhsin (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2022)
One of the characters that became the pillar of the Indonesian nation is religious character. In schools, religious character education is implemented through school culture. School culture is a step to train students through repeated habituation. One of the schools that has implemented religious character education, namely the value of worship and morals through school culture is MI NW Bagik Nyala. However, in its implementation, there are still problems found. This study aims to determine the cultivation of religious character of grade v students through school culture. This research is qualitative research with data collection techniques using observation, interviews, and documentation.The results of this study show that religious character education through school culture in MI NW Bagik Nyala includes a culture of ideas, behavioral culture, and artifact culture in the form of worship and moral values. The strategies used in carrying out religious character education on the value of worship and morals are habituation, example, motivation, and punishment. The problem with character education at MI NW Bagik Nyala comes from the internal students themselves, namely the lack of self-awareness to implement school cultural programs. Thus, it can be concluded that religious character can be formed through school culture if supported by the right efforts and strategies. However, the problems found during the implementation of religious character cultivation cannot be avoided so that the involvement of principals and teachers is needed in religious character cultivation activities through school culture.